2013
DOI: 10.1016/j.bone.2013.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive protein kinase A activity in osteocytes and late osteoblasts produces an anabolic effect on bone

Abstract: Osteocytes have been implicated in the control of bone formation. However, the signal transduction pathways that regulate the biological function of osteocytes are poorly defined. Limited evidence suggests an important role for the G s /cAMP pathway in osteocyte function. In the present study, we explored the hypothesis that cAMP-dependent kinase A (PKA) activation in osteocytes plays a key role in controlling skeletal homeostasis. To test this hypothesis, we mated mice harboring a Cre-conditional, mutated PKA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…Nevertheless, our transgenic models with overexpression of dominant negative mutants offer a unique opportunity to dissect the specific involvement of the two types of channels by Cx43. Specifically, the 10 kb Dmp1 promoter has been extensively used to drive expression/deletion primarily in osteocytes (Kao et al, 2013;Kamiya et al, 2016). In previous immunohistochemical studies of Cx43 transgenic mice, we observed mutant Cx43 protein (GFP-labeled) only in osteocytes, not in other bone cell types.…”
Section: Discussionmentioning
confidence: 69%
“…Nevertheless, our transgenic models with overexpression of dominant negative mutants offer a unique opportunity to dissect the specific involvement of the two types of channels by Cx43. Specifically, the 10 kb Dmp1 promoter has been extensively used to drive expression/deletion primarily in osteocytes (Kao et al, 2013;Kamiya et al, 2016). In previous immunohistochemical studies of Cx43 transgenic mice, we observed mutant Cx43 protein (GFP-labeled) only in osteocytes, not in other bone cell types.…”
Section: Discussionmentioning
confidence: 69%
“…More recently, increased trabecular bone mass and reduced Sost expression were reported in mice specifically expressing a constitutively active form of PKA (CA-PKA) in late osteoblasts and in osteocytes (50). A similar phenotype has been observed in transgenic mice expressing a constitutively active form of PTH1R (CA-PTH1R) in osteocytes (51,52).…”
Section: Discussionmentioning
confidence: 58%
“…Accordingly, it has recently been shown that the increase in bone mass by constitutively active PTH1R depends on Gsα expression in the osteoblast lineage (Sinha, et al 2016). Moreover, in transgenic mice expressing a constitutively active PKA mutant in late osteoblasts and osteocytes, trabecular bone mass is increased and sclerostin expression is reduced (Kao, et al 2013). Expression of the same PKA mutant in mature osteoblasts also lead to increased bone mass with improved bone architecture and mechanical bone properties (Tascau, et al 2016).…”
Section: Gs/camp/pka-mediated Actions Of Pth In Bonementioning
confidence: 99%